SYSTEMATIC LITERATURE REVIEW: MATHEMATICAL COMMUNICATION ABILITY THROUGH QUANTUM LEARNING MODEL BASED ON SELF EFFICACY - Hanif Jauhar Noor; Arief Agoestanto (USN Kolaka, 2023)
Mathematical communication skills are fundamental skills in learning mathematics. Mathematical communication skills are also linked to self-efficacy. This study aimed to determine the improvement and relationship of students' mathematical communication skills using Quantum Learning and self-efficacy. This study used the Systematic Literature Review approach with the PRISMA method. The electronic literature search source used is Google Scholar through Publish or Perish 8, which collects 994 articles, using national and international articles published from 2018-2023, indexed by Sinta 1-4 and indexedby Scopus, categorized as proceedings and journal articles, has full access and is classified as a field of mathematics education. The results showed that self-efficacy affects mathematical communication skills and Quantum learning models, and there is a relationship between self-efficacy and mathematical communication skills with Quantum learning models.